INNOVATION IN VILLAGE GOVERNMENT IMPLEMENTATION MANAGEMENT THROUGH E-VILLAGE BUDGETING (EVB) IN BANYUWANGI REGENCY AND RESTORATION OF VILLAGE ASSET ARCHIVES (REST AREA) IN EAST JAVA PROVINCE - suhendra vmi, adi (Jurnal Studi Inovasi, 2025)
This study is about innovation in strengthening village administration management through E-Village Budgeting (EVB) in Banyuwangi Regency and Village Asset Archive Restoration (REST AREA) in East Java Province. The E-Village Budgeting (EVB) innovation is an online-based village financial management system that includes planning, financial administration, and financial accountability or reporting for villages. The Village Asset Archive Restoration (REST AREA) innovation is an innovation program for preservation, including the handling, repair, and rescue of village asset archives and information. These two innovations have given rise to various strategies that offer conveniences in the administration of village government activities in the areas of financial management and village asset archiving. This study uses a qualitative research approach. Data collection was conducted using the literature review technique. A literature review is a systematic examination of critical scientific literature in analyzing, evaluating, and synthesizing research findings, theories, and practices. A literature review provides an overview of developments in a particular topic. The result of the E-Village Budgeting (EVB) innovation is the creation of a website-based village financial management application to facilitate village governments in an orderly, transparent, and accountable manner in planning, budgeting, administration, accountability, and reporting of village finances in the Banyuwangi Regency ( ). The result of the Village Asset Archive Restoration (REST AREA) innovation is an improvement in the delivery of public services by village governments in East Java Province through an innovation program for the preservation and rescue of high-value village asset archives and the guarantee of protection of the civil rights of the people from the possibility of loss and damage.